Pengaruh Tri Hita Karana Terhadap Minat Wirausaha Generasi Muda di Kabupaten Buleleng - Pureadnyana, Gede; Damayanti, Nyoman Mery; Deivani, Putu Agnes; Sugihantari, Ni Putu Rinasthy Sri; Divayana, Dewa Gede Satya Yoga; Masdiantini, Putu Riesty (Politeknik Negeri Jember, 2024)
Today's young generation faces many economic problems, including high levels of unemployment, competition in the job market, and difficulties in meeting financial needs and expectations. Thus, this study aims to analyse the influence of Tri Hita Karana on the entrepreneurial interest of young people in Buleleng Regency. The population used in this study were all young people in Buleleng Regency. With the number of respondents as many as 90 respondents. Data collection methods in this study using a questionnaire method and reinforced with documentation and interviews. Meanwhile, the data was analysed using multiple linear regression analysis with the help of SPSS (Statistical Product and Service Solution). The results found that partially parahyangan elements have a positive and significant influence on entrepreneurial interest in Buleleng Regency, pawongan elements have a positive and significant influence on entrepreneurial interest in Buleleng Regency, and palemahan elements have a positive and significant influence on entrepreneurial interest in Buleleng Regency.